2013
DOI: 10.5301/ijao.5000237
|View full text |Cite
|
Sign up to set email alerts
|

Using the Impella 5.0 with a Right Axillary Artery Approach as Bridge to Long-Term Mechanical Circulatory Assistance

Abstract: Our experience shows that an Impella 5.0 implanted through the right axillary artery approach is a valid option as bridge to long-term LVADs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…11 This work adds to other evidence that Impella 5.0 is safe for stabilizing patients. 6,12 End-organ function improves and patients can be extubated and ambulated, making them better candidates for advanced therapies and avoiding ventilator-associated pneumonia and adult respiratory distress syndrome. 13,14 In addition, peripheral access avoids multiple chest entries, decreasing the chance of infections and other complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 This work adds to other evidence that Impella 5.0 is safe for stabilizing patients. 6,12 End-organ function improves and patients can be extubated and ambulated, making them better candidates for advanced therapies and avoiding ventilator-associated pneumonia and adult respiratory distress syndrome. 13,14 In addition, peripheral access avoids multiple chest entries, decreasing the chance of infections and other complications.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study indicate that temporary LVAD implantation is a strategy for CS patients that could help decrease morbidity and mortality. 46 …”
mentioning
confidence: 99%
“…A possible advantage of the axillary approach is the potential for long-term support. 52 The proximal 9 Fr catheter shaft houses the motor power leads and purge and pressure measurement lumens. The catheter's proximal end consists of a hub for attachment of a console cable and side arms for attachment of purge solution and pressure-measurement tubing.…”
Section: To Aorta-assist Devicesmentioning
confidence: 99%
“…Previous investigators have reported favorable outcomes when using the Impella 5.0 for postcardiotomy shock, 4 acute cardiogenic shock, 5 acute rejection after heart transplantation, 6 and bridging to durable mechanical circulatory support. 7,8 Avoidance of repeat sternotomy for device exchange has important implications for the patient who is listed for heart transplantation. Prior cardiac surgery not only creates technical challenges during heart transplantation but is associated with increased morbidity and mortality rates after transplantation.…”
Section: Discussionmentioning
confidence: 99%